Dosing antiretroviral medication when crossing time zones: a review. (January 2016) - Lewis, Joseph M.; Volny-Anne, Alain; Waitt, Catriona; Boffito, Marta; Khoo, Saye
Abstract : International tourism continues to increase worldwide, and people living with HIV and their clinicians are increasingly confronted with the problem of how to dose antiretroviral therapy during transmeridian air travel across time zones. No guidance on this topic currently exists. This review is a response to requests from patient groups for clear, practical and evidence-based guidance for travelling on antiretroviral therapy; we present currently available data on the pharmacokinetic forgiveness and toxicity of various antiretroviral regimens, and synthesize this data to provide guidelines on how to safely dose antiretrovirals when travelling across time zones.